2017
DOI: 10.22377/ajp.v11i04.1714
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction: Hydroquinone (HQ), a famous anti-hyperpigmentation agent, suffers from several weaknesses such as instability due to rapid oxidation and insufficient skin penetration because of the hydrophilic structure. The aim of this research was to formulate, characterize and evaluation of in vitro skin permeability of HQ-loaded microemulsion (ME). Methods: HQ MEs were prepared by pseudoternary phase diagram method, the appropriate ratios of oil, s/c mixture, and water were chosen, and full factorial design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…While the ME-S-7 formulation appears to be more effective in the transdermal delivery of SC, further investigation is needed. The inclusion of an optimal amount of CS, acting as a penetration enhancer, may contribute to the higher permeability of SC through the skin, as observed with SC-ME7 (29). Therefore, the reduced steady-state flux (J ss ) parameter in other formulations might result from a non-optimal amount of PG despite similar oil and water proportions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the ME-S-7 formulation appears to be more effective in the transdermal delivery of SC, further investigation is needed. The inclusion of an optimal amount of CS, acting as a penetration enhancer, may contribute to the higher permeability of SC through the skin, as observed with SC-ME7 (29). Therefore, the reduced steady-state flux (J ss ) parameter in other formulations might result from a non-optimal amount of PG despite similar oil and water proportions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, both the J ss and the permeability coefficient through rat skin increased for all SC-ME samples. Typical enhancers can enhance the skin permeation rate of drugs by optimizing permeability parameters based on specific structural properties (29). The ME systems have shown great potential for the topical administration of therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The permeability coefficient and flux from the rat skin increased significantly in all ME formulations with different features and compositions. In addition, several studies have confirmed the advantages of ME vehicles as promoters of dermal delivery (23,25), which can increase skin permeation by changing drug diffusion or partitioning coefficient (22).…”
Section: Me-k-6mentioning
confidence: 96%
“…According to previous studies, the S/C content in ME vehicles majorly influences the skin permeation of hydroquinone (23). Glycols (PEG400) can improve skin permeation through different mechanisms, including lipid and protein extraction, swelling of the stratum corneum, enhancing drug partitioning into the skin, and improving drug solubility in the formulation (22).…”
Section: Me-k-6mentioning
confidence: 99%